ETNOEKOLOGI PERLADANGAN DAN KEHILANGAN KARBON DI AREAL KONSESI PT. SARI BUMI KUSUMA KALIMANTAN TENGAH (Studi Kasus Masyarakat Dayak Pangin, Dohoi, dan Melahui) - , WAHID ADI WIBOWO; , Prof. Dr. Ir. San Afri Awang, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Farming is one kind of interaction between native Dayak people and forests. This interaction has been long established, since their ancestor occupied the upstream of Katingan, Seruyan, and Senamang River. However, as the development time comes followed by the arrival of PT. Sari Bumi Kusuma with its forest management license holder within Dayak community area, farming activities by native people have changed their meaning. The research aims: 1) to obtain information about the cultivation ethnoecology of Dayak community living in the concession area of PT. Sari Bumi Kusuma, 2) to project land needs, 3) to assess the potential of biomass, carbon, and COÂ² absorption yield from rubber planting and the lost of biomass, carbon, and COÂ² sequestration due to farming activities. The method used in the research is ethnographic methods by James Spreadley. The research was conducted in three villages, namely, Tanjung Paku, Tumbang Karuei, and Kiham Batang. Participatory observa tion means that researcher lives in natural setting and participates in activities undertaken by local community. Primary data collection was conducted by open interview and in depth interview. Key informants were selected by reference, and further informants were selected through snowball method. The collected data was analyzed by qualitative analysis. Cultivation projection was built using Idrisi Taiga software. Projection method is conducted in line with the Markov law. Carbon accounting was measured with allometric equations. Secondary data and cultivation projection map in 2019 were used as inputs to measure carbon. The result showed that: 1) The process of Dayak farming consists of seven activities (7M), which are: determining the location, slashing, cutting, burning, planting, maintening, and harvesting, 2) Local Wisdom is used in managing the fields such as rules and customary rites to determine fieldsâ location and drain the land, and the use of natureâs sign as an indicator of pests and diseases, bawas system, and land tenure, as well as the absence of chemical fertilizers and pesticides, 3) Factors that influence cultivation activities such as nature, population growth, limited business opportunity, interaction with outsiders, and technology development, 4) Total area of projected field in 2019 are 18.099 ha, 5) Carbon sequestration potential of rubber planting by communities is 60.726 tons, while the carbon loss from cultivation activities is estimated at 291.897 tons.